Fat mass and obesity‐associated gene variations are related to fatty liver disease in HIV‐infected patients. Issue 8 (24th January 2017) - Núñez‐Torres, R; Macías, J; Rivero‐Juarez, A; Neukam, K; Merino, D; Téllez, F; Merchante, N; Gómez‐Mateos, J; Rivero, A; Pineda, JA; Real, LM; ,
Abstract : Objectives: Fatty liver disease (FLD) is frequently observed in HIV‐infected patients. Obesity and type 2 diabetes mellitus (T2DM) are strongly associated with FLD. Because genetic variants within the fat mass and obesity‐associated ( FTO ) gene have been associated with both pathologies, our aim was to evaluate the association of single nucleotide polymorphisms (SNPs) within the FTO, previously related to obesity or T2DM, with FLD in HIV‐infected patients. Methods: FLD was defined as a value of the controlled attenuation parameter (CAP) ≥ 238 dB/m, obtained by transient elastography. Four SNPs within FTO intron 1 (rs11642841, rs8050136, rs9939609 and rs9940128) were genotyped in 421 individuals using a custom Golden Gate protocol. The results were replicated in a validation sample consisting of a further 206 HIV‐infected patients. Multivariate logistic regression analyses were conducted in the entire population. Results: Three SNPs (rs8050136, rs9939609 and rs9940128) were associated with FLD, with rs9940128 showing the strongest association. This polymorphism also showed an association with FLD in the validation sample. In total, rs9940128 was genotyped in 627 HIV‐infected patients, including 267 (42.6%) FLD‐diagnosed individuals. The frequency of FLD among rs9940128 AA carriers was 55.7% (63 of 113 individuals) and that in patients without this genotype was 39.7% (204 of 514 individuals) [ P = 0.009; adjusted odds ratio 1.88; 95% confidence interval (CI) 1.17–3.01]. Conclusions: Variations within FTO may be predictors of FLD in HIV‐infected patients independently of metabolic factors.